FORMULASI NANOEMULGEL MINYAK ATSIRI DAUN MINT (Mentha piperita L.) - Fauzan Ashari Nur H; Disa Andriani (Universitas Pekalongan, 2025)
Peppermint (Mentha piperita L.) essential oil exhibits therapeutic activities such as anti-inflammatory, analgesic, antioxidant, and antimicrobial effects, making it a potential active ingredient for topical pharmaceutical and cosmetic products. However, essential oils are highly volatile, resulting in instability and limited effectiveness. A nanotechnology-based approach, particularly nanoemulsion systems, has emerged as an effective strategy to improve stability, bioavailability, and skin penetration of essential oils. This study aimed to evaluate the particle size and physical properties of nanoemulgel formulations that meet acceptable quality requirements. Peppermint leaf essential oil was formulated into nanoemulgel preparations at a concentration of 5% in Formula 1 and 10% in Formula 2, followed by evaluation of particle size and physical characteristics. The results of the physical characterization showed that the nanoemulsion particle size was 111.66 ± 2.35 nm for Formula 1 and 134.06 ± 3.31 nm for Formula 2. All physical property evaluations of the nanoemulgel formulations met the requirements for a good gel preparation Keywords: peppermint leaf essential oil, nanoemulgel, physical properties, nanoparticle size